2023
DOI: 10.1002/adma.202300850
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Superfilling Construction of a Metal Artificial Interface for Long‐Term Stable Zinc Anodes

Abstract: Zinc (Zn)‐metal anodes are promising candidates for large‐scale, highly safe energy‐storage systems. However, their cycling life is associated with instability issues such as dendritic growth, corrosion, and hydrogen evolution. Introducing an artificial metal interface is expected to help overcome this challenge owing to the optimization of the absorption, nucleation, and growth of Zn2+. In this study, an ultrafast, universal, and cost‐effective superfilling approach is developed to construct a metal artificia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…In order to investigate the regulating effect of the Zn-CCS polymer crowding layer more deeply, chronoamperometry (CA) was applied to analyze the Zn deposition behavior under the three-electrodes system. When the potential was 150 mV, the current on the bare Zn surface increased rapidly and irregularly, and the Zn underwent 2D-directional diffusion and uncontrollable disorderly deposition within 1000 s. In contrast, Zn-CCS polymer crowding layer regulated the diffusion and Zn deposition behavior at the zinc anode interface, and rapidly induced the deposition of Zn 2+ at a stable current, which promotes the uniform deposition of zinc anode (Figure j). , Zn-CCS polymer crowding layer with solid electrolyte chemistry was also a favorable physical barrier; the Tafel test showed that Zn-CCS polymer crowding layer could also play a multifunctional performance in regulating Zn ion transport and deposition by reducing corrosion current (2.218 mA) and corrosion potential (−0.977 V), which was also consistent with its weak adsorption ability to anions as mentioned previously. , The results suggested that the abundant functional groups on the Zn-CCS polymer crowding layer confer excellent ion conductivity, modulation of Zn 2+ kinetic behavior, and enhancement of corrosion resistance.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the regulating effect of the Zn-CCS polymer crowding layer more deeply, chronoamperometry (CA) was applied to analyze the Zn deposition behavior under the three-electrodes system. When the potential was 150 mV, the current on the bare Zn surface increased rapidly and irregularly, and the Zn underwent 2D-directional diffusion and uncontrollable disorderly deposition within 1000 s. In contrast, Zn-CCS polymer crowding layer regulated the diffusion and Zn deposition behavior at the zinc anode interface, and rapidly induced the deposition of Zn 2+ at a stable current, which promotes the uniform deposition of zinc anode (Figure j). , Zn-CCS polymer crowding layer with solid electrolyte chemistry was also a favorable physical barrier; the Tafel test showed that Zn-CCS polymer crowding layer could also play a multifunctional performance in regulating Zn ion transport and deposition by reducing corrosion current (2.218 mA) and corrosion potential (−0.977 V), which was also consistent with its weak adsorption ability to anions as mentioned previously. , The results suggested that the abundant functional groups on the Zn-CCS polymer crowding layer confer excellent ion conductivity, modulation of Zn 2+ kinetic behavior, and enhancement of corrosion resistance.…”
Section: Resultsmentioning
confidence: 99%
“…One routine, facile way for SEI introduction is to physically coat functional materials onto Zn surface. It has been demonstrated that the presence of metals (Sn, [5] Ag, [6] etc. ), inorganic salts (ZnSnO 3 , [7] Zn y O 1‐x F x , [8] etc .)…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Amongst these strategies, the protective layer approach holds the advantages of simple operation, controllable cost, and no sacrifice of intrinsic capacity. [15,16] So far, a rich variety of materials like carbonbased materials, [17,18] metals, [19,20] metal oxides [21,22] and polymers [23,24] have been designed as coatings for the Zn anode. Notably, polymer coatings have shown prominent interfacial compatibility and readily tunable structures.…”
Section: Introductionmentioning
confidence: 99%